2011
DOI: 10.1242/dev.067041
|View full text |Cite
|
Sign up to set email alerts
|

tcf21+ epicardial cells adopt non-myocardial fates during zebrafish heart development and regeneration

Abstract: SUMMARYRecent lineage-tracing studies have produced conflicting results about whether the epicardium is a source of cardiac muscle cells during heart development. Here, we examined the developmental potential of epicardial tissue in zebrafish during both embryonic development and injury-induced heart regeneration. We found that upstream sequences of the transcription factor gene tcf21 activated robust, epicardium-specific expression throughout development and regeneration. Cre recombinase-based, genetic fate-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
345
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(366 citation statements)
references
References 34 publications
19
345
2
Order By: Relevance
“…It has been shown that epicardial cells are activated early after cryoinjury and partially repopulate the damaged area by 3 dpi (5, 6). To investigate whether any epicardial cells could be observed in the injured area by 15 hpi, we cryoinjured fish harboring the tcf21:DsRed2 transgene, which labels epicardial and epicardiumderived cells (EPDCs) (14). However, at 15 hpi, we did not observe any DsRed + cells in the damaged region, indicating that blood vessels enter the injury site before EPDCs (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that epicardial cells are activated early after cryoinjury and partially repopulate the damaged area by 3 dpi (5, 6). To investigate whether any epicardial cells could be observed in the injured area by 15 hpi, we cryoinjured fish harboring the tcf21:DsRed2 transgene, which labels epicardial and epicardiumderived cells (EPDCs) (14). However, at 15 hpi, we did not observe any DsRed + cells in the damaged region, indicating that blood vessels enter the injury site before EPDCs (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Similar to the myocardium, following-injury epicardial cells exhibit morphological changes and reexpress developmental genes including raldh2 and tbx18 (11,12). The epicardium gives rise to myofibroblasts and perivascular cells (13,14), and epicardium-derived perivascular and smooth muscle cells support revascularization of the injured area in zebrafish and mammals (15,16). Following injury, new coronary vessels penetrate the damaged area (5,12,16) where the main source of new coronary endothelium is preexisting endothelium (17).…”
mentioning
confidence: 99%
“…30 In embryos, the hypothesis of an alternative source for supplying cardiac progenitor cells from the epicardium was denied by a lineage-tracing study, confirming the possibility that the mechanism for embryonic heart growth is similar to that of juveniles. 31 What causes the heart failure response?…”
Section: Multiple Stressors Converge To Halt Cardiomyocyte Proliferationmentioning
confidence: 99%
“…Zebrafish hearts can fully regenerate within a period of 30 to 60 days after surgical removal of as much as 20% of the ventricle [71], a cryoinjury or a genetic ablation of over 60% of the cardiomyocytes [77 80]. Cardiac regeneration in adult zebrafish is not achieved by proliferation and differentiation of cardiac stem cells, as initially suggested, but by activation, de-differentiation and proliferation of mature cardiomyocytes [75,76,81]. After de-differentiation, cardiomyocytes undergo a subsequent maturation step to completely restore cardiac function.…”
Section: Epicardium and Cardiac Regenerationmentioning
confidence: 99%
“…After de-differentiation, cardiomyocytes undergo a subsequent maturation step to completely restore cardiac function. Ultimately, newly generated cardiac myocytes are functionally integrated with the preexisting myocardium with little or no evidence of the injury, suggesting complete myocardial regeneration [75,76,81]. These studies have encouraged scientists to determine whether the adult mammalian heart is incapable of cardiac myocyte replacement or whether it retains a low-level capacity for regeneration, which could be therapeutically amplified.…”
Section: Epicardium and Cardiac Regenerationmentioning
confidence: 99%